Analisis Karakter dan Persepsi Wisatawan Mancanegara Terhadap Produk Wisata di Kawasan Prawirotaman - , Reiza Miftah Wirakusuma ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted on the fact that Prawirotaman, Yogyakarta has been well known as a tourist attraction since 1974. The power of historical value, Batik Craftsmen and relaxed atmosphere generate the value of the accommodation which was very precious to be a tourist attraction. What is the current conditions nowadays, with the rapid improvement of technology and increasing of numerous new hotel in Yogyakarta? This study will reveal what affect foreign tourists for coming to Prawirotaman. The objectives of this research is to identify profile and character of foreign tourists from psychography, geography, and demography segmentation as well as tourism trend. Next, to identify the perception of foreign tourists from tourist attraction, accesibility, amenities, price, service quality, advertising, number of visit, length of stay, and expenditure. Last, to identify which factor is the most influencing foreign tourists perception in Prawirotaman. The research methods that have been used such as quantitative in multiple regression analysis and qualitative in analysis descriptive. These findings generated the biggest 5 market by nationality such as Netherland, Germany, France, USA and Japan. From the analysis can be concluded that (1) There is an existence of the partial effect between variable of attraction with tourist arrivals. This emphasizes that variable of attractions is influencing independently without other variables. Furthermore, it is also indicating that the power of Prawirotaman is an affordable international culinary complex with afforadble price as well as serenity ambience and various types of accommodation. (2) The character of foreign tourists affect the combination of tourism products offered by Prawirotaman Tourism Operators (Hotels, Travel Agents, Restaurants). As the highlight, the characters of foreign tourists are more influenced by demographic segmentation in choosing travel patterns.